2017
DOI: 10.1101/153510
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LPP3 mediates self-generation of chemotactic LPA gradients by melanoma cells

Abstract: Melanoma cells steer out of tumours using self-generated lysophosphatidic acid (LPA) gradients. The cells break down LPA, which is present at high levels around the tumours, creating a dynamic gradient that is low in the tumour and high outside. They then migrate up this gradient, creating a complex and evolving outward chemotactic stimulus. Here, we introduce a new assay for self-generated chemotaxis, and show that raising LPA levels causes a delay in migration rather than loss of chemotactic efficiency. Knoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Interestingly, some phospholipases are secreted proteins (Park et al, 2012), suggesting that cancer cells actively modify the tumor microenvironment lipidome. Lysophospholipids produced by these secreted phospholipases can be further converted to the signaling molecule LPA by extracellular ATX/ ENPP2 (Federico et al, 2016), producing a chemotactic gradient that promotes dissemination of melanoma cells (Susanto et al, 2017). Similarly, it was recently shown that pancreatic stellate cells release lysophospholipids, which are converted to LPA by ATX/ENPP2 and promote progression in pancreatic cancer (Auciello et al, 2019).…”
Section: Heterotypic Interactions In the Tumor Microenvironmentmentioning
confidence: 99%
“…Interestingly, some phospholipases are secreted proteins (Park et al, 2012), suggesting that cancer cells actively modify the tumor microenvironment lipidome. Lysophospholipids produced by these secreted phospholipases can be further converted to the signaling molecule LPA by extracellular ATX/ ENPP2 (Federico et al, 2016), producing a chemotactic gradient that promotes dissemination of melanoma cells (Susanto et al, 2017). Similarly, it was recently shown that pancreatic stellate cells release lysophospholipids, which are converted to LPA by ATX/ENPP2 and promote progression in pancreatic cancer (Auciello et al, 2019).…”
Section: Heterotypic Interactions In the Tumor Microenvironmentmentioning
confidence: 99%
“…Media samples were harvested every 12 h for 96 h. Prior to butanol extraction, 0.5mg of synthetic 17:0 LPA (Avanti) was added to samples. Liquid chromatography-mass spectrometry analysis was based on Susanto et al (2017). Lysophosphatidic acids (LPAs) were analyzed using a Q-Exactive Orbitrap mass spectrometer coupled to an UltiMate 3,000 LC system (Thermo Scientific).…”
Section: Traction Force Microscopymentioning
confidence: 99%
“…Lysophosphatidic acid (LPA) is a naturally producing lipid that can modulate cell migration during development and cancer (1)(2)(3). In many cancer cell types, such as breast cancer (1), ovarian cancer (4), melanoma (5), prostate cancer (6), and pancreatic cancer (7), LPA exhibits the ability to promote migration. Besides migration, several other aspects of tumor biology including proliferation, and invasion, angiogenesis are also coordinated by LPA in restricted cancer types (8).…”
Section: Introductionmentioning
confidence: 99%